(untitled) (Scientific journal of the Fergana State University, 2023)
In the article, the views of linguists on the theory of language and speech, as well as the functions of the speech act in pragmatics, which is one of the main fields of modern linguistics, and the research conducted on the categories of pragmatic competence, are researched into the context of the imperative speech act. Also, the article analyzes theoretical ideas about the imperative speech act based on examples taken from works of art.